Analysis of Garlic Import Demand Trend in Indonesia - Purba, Pesta; Yuliarti, Ellys; Sukiyono, Ketut (Indonesian Journal of Agricultural Research, 2022)
This research aims to find out the development patterns and trends in import demand for garlic in Indonesia. Observing the pattern and trend of garlic imports will provide invaluable information for program planning, program evaluation, and policy development activities for domestic garlic development in the future. The data used in this study is the annual demand for garlic imports in Indonesia from 1995-2019. Three trend methods are applied including linear, quadratic, and exponential methods. The best trend was determined by examining the MAD, MES, ME, and MAPE values. The best trend model for garlic import demand in Indonesia, according to this study, is an ascending exponential trend. The trend of garlic import demands in Indonesia increases along with the increase of garlic consumption and domestic garlic production in Indonesia.